Exploring the Narrative Spaces of Change in Jejak Warna: Cerita tentang Perubahan (2019) Web Series: - - Aidatul Chusna; Budi Irawanto; Dian Arymami (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
Jejak Warna: Cerita tentang Perubahan (Color Trail: A Story of Change) web series talks about a man named Arya who is stuck with his monotonous life and memory of his ex-girlfriend. His life changes when he meets Kinar – his new colleague. This study explores how the narrative space conveys the idea of change by analysing the mise-en-scène elements of the web series. The result shows the depiction of spaces which change from spaces that bind the protagonist in his dull routine and memory to a space that liberates and offers him new life and adventure. The change is strengthened by the changing nuances of spaces depicted through composition and lighting, sound (dialogue and music), and the character's expression and movement within the spaces.